“If I Stop Now What Will Happen Later?”: The Lived Experiences of Teenage Moms as Students and Mothers in Cebu City during the Pandemic - Amolo, Raiza Mae; Calamohoy, Don Eric; Congson, Jan Carylle; Cubillan, Gregory John; Gingoyon, Hazel Mae; Lanticse, Chloe; Lausa, Jan Mark; Tajanlangit, Lorraine Belle; del Socorro, Celeste; Gagani, Flordeliza (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This phenomenological study was conducted to give a platform and to amplify the voices of teenage mothers who were at the same time studying during the COVID-19 pandemic. This study was conducted in Cebu City, Philippines in 2022 having teen mothers as the participants of the study employing non-probability sampling. Using Colaizzi's descriptive analysis method to evaluate transcripts of online interviews with five selected participants, the researchers identified five major themes that accurately portrayed the highlights, challenges, coping mechanisms, and overall meanings of participants' experiences. The five major themes were: (1) “Choose The Right Partner!”: Having Company; (2) “The One That Changes Me”: The Effect of Motherhood; (3) “Student/Mother/Father/Daughter”: Conflict in a Routine; (4) “If I Stop Now, What Will Happen Later?”: The Value of Education; (5) “Survival of the Fittest”: Me and My Future. The researchers discovered that teenage mothers in this situation benefit greatly from supportive relationships, form strong attachments to their children, face numerous conflicts in different aspects of their lives, value education highly, and have optimistic views of their futures and of themselves. With these results in mind, the researchers strongly recommend more programs to be implemented and policies to be developed to encourage teenage mothers to re-engage with education, especially knowing the factors that may contribute to a more positive experience.